2021
DOI: 10.33403/rigeo.724741
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Publications in the Field of Geography Education: Bibliometric Analysis Based on the Web of Science Database

Abstract: The purpose of this study is to examine scientific publications about Geography Education in terms of bibliometric indicators. Case study method, one of the qualitative research methods, was applied in this study. The scanning range of bibliometric data obtained from the WoS database generated by Clarivate Analytics covers the dates between 1975 and March 2020. The bibliometric analysis technique was conducted in the study. As a result of the analyses, it was revealed that 559 of 64,874,978 studies registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…88% of the academic studies on the use of technology in geography education are conducted in English, while 8% are carried out in Portuguese and 2% are conducted in Spanish. Sönmez et al, [32] in their bibliometric analysis study on geography education, examined the distribution of academic studies by languages and obtained similar findings. When the findings of both bibliometric studies are taken into consideration, it can be concluded that English is the most preferred language in conducting research on geography education.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…88% of the academic studies on the use of technology in geography education are conducted in English, while 8% are carried out in Portuguese and 2% are conducted in Spanish. Sönmez et al, [32] in their bibliometric analysis study on geography education, examined the distribution of academic studies by languages and obtained similar findings. When the findings of both bibliometric studies are taken into consideration, it can be concluded that English is the most preferred language in conducting research on geography education.…”
Section: Resultsmentioning
confidence: 79%
“…It is believed that the use of technology in geography education will gain more significance depending on the increasing number of publications and citations in the following years. Sönmez et al, [32] in their bibliometric analysis study, examining the publications on geography education, revealed that the number of publications and citations indexed by Web of Science increased over the years. In a similar line, the bibliometric analysis study by Melo and Queiroz [33], on geographic information systems between 2007 and 2016 revealed an increase in the number of publications over the years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation